EXPLORING STUDENTS' READING STRATEGY IN ENGLISH SUBJECT AT SMP NEGERI 17 BAUBAU - Rizal Arisman (English Education Journal, 2022)
The problem statement of this research was whether the dominant reading strategy used by grade eight students at SMP Negeri 17 Baubau. From the problem statement, this research aims to know the dominant reading strategy in English subject activity used by grade eight students at SMP Negeri 17 Baubau Data collection in this research was carried out using a research instrument in the form of a questionnaire to determine the category of students' reading strategy. The data obtained were analyzed by descriptive statistics. The result indicated that the mean score for the metacognitive reading strategy was 2.79, the mean score for the cognitive reading strategy was 2.81, and the social reading strategy was 2.61. From those results, it could be concluded that the dominant reading strategy used by grade eight students was the cognitive strategy.